satellite velocity on elliptical orbit is
"v^2=GM(\\frac{2}{r}-\\frac{1}{a})"but for apogee this this equation is
"r=a(1+e)"
for perigee
"r=a(1-e)""v_P^2=\\frac{GM}{a} \\times\\frac{(1+e)}{(1-e)}"
Thus
"\\frac{v_A^2}{v_P^2}=\\frac{\\frac{GM}{a} \\times\\frac{(1-e)}{(1+e)}}{\\frac{GM}{a} \\times\\frac{(1+e)}{(1-e)}}"we have
"v_A=\\frac{(1-e)}{(1+e)}\\times v_P"finally using initial conditions, we have
"v_A=\\frac{1}{3}\\times v"satellite velocity at apogee is three times less than perigee
Comments
Leave a comment